Educational outreach and collaborative care enhances physician's perceived knowledge about Developmental Coordination Disorder - Missiuna Cheryl; Gaines Robin; Egan Mary; McLean Jennifer (BMC, 2008)
Abstract Background Developmental Coordination Disorder (DCD) is a chronic neurodevelopmental condition that affects 5-6% of children. When not recognized and properly managed during the child's development, DCD can lead to academic failure, mental health problems and poor physical fitness. Physicians, working in collaboration with rehabilitation professionals, are in an excellent position to recognize and manage DCD. This study was designed to determine the feasibility and impact of an educational outreach and collaborative care model to improve chronic disease management of children with DCD. Methods The intervention included educational outreach and collaborative care for children with suspected DCD. Physicians were educated by and worked with rehabilitation professionals from February 2005 to April 2006. Mixed methods evaluation approach documented the process and impact of the intervention. Results Physicians: 750 primary care physicians from one major urban area and outlying regions were invited to participate; 147 physicians enrolled in the project. Children: 125 children were identified and referred with suspected DCD. The main outcome was improvement in knowledge and perceived skill of physicians concerning their ability to screen, diagnose and manage DCD. At baseline 91.1% of physicians were unaware of the diagnosis of DCD, and only 1.6% could diagnose condition. Post-intervention, 91% of participating physicians reported greater knowledge about DCD and 29.2% were able to diagnose DCD compared to 0.5% of non-participating physicians. 100% of physicians who participated in collaborative care indicated they would continue to use the project materials and resources and 59.4% reported they would recommend or share the materials with medical colleagues. In addition, 17.6% of physicians not formally enrolled in the project reported an increase in knowledge of DCD. Conclusion Physicians receiving educational outreach visits significantly improved their knowledge about DCD and their ability to identify and diagnose children with this condition. Physicians who collaborated with occupational therapists in providing care reported more confidence in diagnosing children with DCD and were more likely to continue to use screening measures and to provide educational materials to families.